Ablation behavior of graphite/SiO2 composite irradiated by high-intensity continuous laser. Issue 4 (April 2017) - Li, Wenzhi; Gao, Lihong; Ma, Zhuang; Wang, Fuchi
Abstract: Graphite and SiO2 composite was prepared by hot-pressing at 1300 °C for 3 h under a uniaxial load of 20 MPa. The ablation behavior of graphite and SiO2 composite by high-intensity continuous laser was investigated. The X-ray diffraction, scanning electron microscopy, 3D-super-depth-digital microscopy, Raman spectroscopy and reflectivity were used to characterize the sample. The results show that under low laser power (500 W/cm 2 ), and no obvious damage appears, while just the irradiation area changes from grey to white and the reflectivity increases. With the laser power increasing, some heat-absorbing chemical reactions between graphite and SiO2 occurred on the surface, and SiC was produced, which can increase the energy consumption of the surface and thus reduce the absorbed laser energy of the interior. Moreover, at the center of irradiation area, the formation of columnar structure graphite is beneficial to obstruct laser energy conduction from surface to interior material.